The development of Traditional Chinese Medicine home nursing based on Internet Plus (基于“互联网+”的家政式中医护理服务的发展趋势) - TIAN Guo (田果); WU Cuicui (吴翠翠); ZHANG Chengjuan (张诚娟); LUO Fanwei (罗凡威); LONG Yeyun (龙叶运); CHEN Ying (陈英) (中西医结合护理)
Based on the Traditional Chinese Medicine nursing, Traditional Chinese Medicine home nursing is an Internet-Plus-Nursing-oriented service which is designed to meet the health and life care of patients and general population. This paper summarized the concepts and significance of Internet Plus in promotion of Traditional Chinese Medicine nursing, and discussed its potential demands, and provided reference for the promotion of Traditional Chinese Medicine home nursing based on Internet Plus. (家政式中医护理特色服务是以“互联网+护理”为导向, 以中医护理服务为主基调, 为罹患疾病的患者提供护理服务, 顺应健康人群对健康和养生保健的要求。本文从普及“互联网+”的含义及重要性入手, 增强“互联网+”的认识, 并挖掘其内在的需求, 从而推动基于“互联网+”的家政式中医护理特色服务的实施。)